A SCOPING REVIEW STUDY ON VICTIMS OF SEXUAL OFFENCES EXPERIENCES UNDERGOING THE POST-SEXUAL ASSAULT CARE SERVICES OFFERED BY THE SELECTED RELEVANT STAKEHOLDERS - Linda Moloko Seomane (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This scoping review study explores the experiences of victims of sexual offences with post-sexual assault care services provided by the Thuthuzela Care Centres (TCCs) and the Local South African Police Service (SAPS). Using the methodology framework by Arksey, H and O'Malley, L (2005). It was qualitative in nature, retrieving about 503 articles from the following Social Sciences databases, the Science Direct and Google Scholar EbcoHost, Internet sources, and ProQuest, amongst others. However, only Nineteen (19) articles met the inclusion/eligibility criteria. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), together with the inductive Thematic Content Analysis (TCA) were used to analyse the data. The study findings revealed both satisfaction and dissatisfaction experiences with these service providers, highlighting areas that requires improvement. The interactions with TCCs were generally positive, with high rates of reported professionalism, empathy, immediate attention from staff and victim-centred environment. However, the interactions with police officers were frequently negative, with survivors describing experiences of secondary victimisation, lack of sensitivity, disrespect, apathy, and lack of case follow-up. The provision of medical care was prioritised in terms of the Human Immunodeficiency Virus (HIV) testing and Post-Exposure Prophylaxis (PEP) treatment and treatment for prevention of pregnancy and Sexually Transmitted Diseases (STIs) continuity of care was inconsistent. Mental healthcare was inadequately addressed in terms of long-term counselling services and continuous follow-ups appointments. This study also highlights the need for trauma-informed training and victim-centric improvements within the local SAPS. It is recommended that the training for new SAPS recruits include a formal trauma-debriefing course to assist new recruits to have more in-depth understanding of how a traumatic experience such as rape affects victims and how police behaviour affects victims' trauma.